Implikasi dan problematika pernikahan usia dini: Perspektif sosial dan pendidikan di Indonesia - Muzaki, Muhammad (Maliki Interdisciplinary Journal, 2024)
Early marriage is a complex phenomenon that has a significant impact on social and educational aspects in Indonesia. This article discusses the implications and problems of early marriage from a social and educational perspective. Early marriage, which involves individuals under the age of 19, often violates women’s rights and can interfere with parenting in the family. Education has also been affected, with many children dropping out of school as a result of early marriages. Solutions to overcome early marriage include disseminating laws related to child marriage, strengthening the family economy to reduce economic pressure, and early education and promotion of gender equality to change social norms that support early marriage. With this action, it is hoped that the Indonesian people can protect children’s rights, reduce early marriages, and promote sustainable development both individually and society as a whole.